DESCRIPTION OF THE EXPERTISE OF MATHEMATICS EDUCATION LECTURERS AT RIAU ISLAMIC UNIVERSITY BASED ON PUBLICATION WORKS: SYSTEMATIC LITERATURE REVIEW: Mathematical Errors; Story Problems; Relationships; Polya Stages - Istikomah, Endang; Abdurrahman Abdurrahman; Nurvani Yulia Dewi; Sevilla Atita Azzahra (Mathematics Research and Education Journal, 2025)
This study aims to analyze the types of errors made by female students in solving mathematical story problems on the topic of relations using Polya’s problem-solving stages. Employing a qualitative descriptive approach, the research involved 30 eighth-grade students from SMP Al-Faruqi. Data were collected through written tests and interviews, then analyzed through data reduction, data presentation, and conclusion drawing. The findings revealed that errors occurred in all stages of Polya’s framework, with 50% of students making errors in understanding the problem (moderate category), 47.7% in planning (moderate), 63.3% in implementing the plan (high), and 26.7% in rechecking (low). The most frequent error was found in the implementation stage, indicating that while students could generally comprehend and plan problem solutions, they often faced difficulties in accurately executing those plans. This suggests that female students still need to strengthen their procedural understanding and problem-solving execution skills to improve overall mathematical performance, particularly in applying strategies effectively and verifying their solutions.